Assessment of the basaltic rocks in Yemen for the basalt fibers production (Thamar University Journal of Natural & Applied Sciences, 2024)
Representative samples were collected from 22 sites across Yemen. The geochemical analysis found that the SiO2 content ranges from 40.40 to 55.60%, the Al2O3 content ranges from 12.70 to 16.10%, the Fe2O3 content ranges from 8.41 to 15.80%, the CaO content ranges from 3.66 to 11.05%, and the MgO content ranges from 1.30 to 11.40%. TiO2 content ranges from 1.11 to 5.56%, NaO2 content from 1.88 to 4.88%, and K2O content from 0.67 to 3.25%. The calculations of the acidity, viscosity modules and fusibility constant of the investigated rocks showed the suitability of the basaltic rocks locations for the production of basalt fiber, except the Hajda, Mafraq Al Makha, Karish, Wadi Al Jima, and Wadi Qaradh locations, as a result of the high acidity module The results of the geochemical analysis of the studied samples were compared with the geochemical analyses of similar rocks from different countries used in basalt fiber production. The comparison showed significant similarities in the results, indicating that the studied rocks are suitable for basalt fiber production. A petrographically study on basalt rocks after they melted at temperatures ranging between 1190 and 1240 °C, and it was found that they consist mainly of basalt glass. Melting experiments were carried out, which showed that the beginning of the fusion was at a temperature ranging between 1030 and 1150 °C, and the fusion was completed at a temperature ranging between 1200 and 1220 °C, while the temperature at which the crystallization process began was at a temperature ranging between 1190 and 1200 °C. The study concluded that the studied basalt rock sites are suitable for manufacturing basalt fiber.